Implementasi Kebijakan Pembuatan Kartu Identitas Anak di Kota Bandar Lampung - Andre Ridho Illahi; Dian Kagungan; Vina Karmilasari (Jurnal Administrativa, 2023)
Population data collection is one of the rights that must be fulfilled by a country. Realizing this, the Indonesian government also conducted data collection by requiring people over the age of 17 to produce an e-KTP, while for people under 17 the Ministry of Home Affairs has issued Permendagri No. 2 of 2016 concerning Identity Cards. as a fulfillment of children's rights to obtain a legal identity and has integrated the population administration information system (SIAK) and requires children throughout Indonesia to make an identity card in the form of MCH which is carried out by the Disdukcapil of Bandar Lampung City as one of the implementers of the policy. This study aims to describe how the implementation of the policy of making child identity cards in Bandar Lampung City. This study uses theory to measure the level of success of implementation according to Charles O. Jones, namely by looking at how it is organized, interpreted and applied. This type of research is descriptive research with a qualitative approach using data collection techniques with interviews, documentation and observation and using data analysis techniques with data presentation, data reduction, and drawing conclusions. The results of this study indicate that the implementation of the policy of making child identity cards in Bandar Lampung City which has been carried out by the Department of Population and Civil Registry of Bandar Lampung City has been going well but there are still factors that hinder implementation such as lack of socialization and several other problems.